1967
DOI: 10.1016/0021-9681(67)90009-4
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of the prevalence of rheumatic diseases in the population of Tecumseh, Michigan, 1959–60

Abstract: THE TECUMSEH COMMUNITY HEALTH STUDY (TCHS) was not undertaken solely as a rheumatic disease survey but as a broad study of health and disease in a total community setting. [l, 21 It was conceived as a continuing dynamic study of the multitude of natural processes and interactions which are responsible for the maintenance of health or the development of disease. Interest has centered not so much on the identification of established disease as on the possibility of elucidating the early origins of disease and id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0
5

Year Published

1975
1975
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(44 citation statements)
references
References 26 publications
3
33
0
5
Order By: Relevance
“…In women, RA prevalence ranged from 2.35% to 2.71%, and in men, it ranged from 1.60% to 1.85%. In the Tecumseh Community Health Study (conducted from 1959 to 1960), the prevalence of definite RA in persons ages 60 years and older was ϳ1% for men and ϳ2% for women, as defined by the ACR 1958 criteria (33). In a recent review of RA prevalence in the US, Lawrence and colleagues (13) reported that in the National Health Examination Survey (for the years 1960-1962), definite RA was identified in 1.8% of men and 4.9% of women between the ages of 65 and 79 years, using the ACR 1958 criteria for definite and classic RA.…”
Section: Discussionmentioning
confidence: 99%
“…In women, RA prevalence ranged from 2.35% to 2.71%, and in men, it ranged from 1.60% to 1.85%. In the Tecumseh Community Health Study (conducted from 1959 to 1960), the prevalence of definite RA in persons ages 60 years and older was ϳ1% for men and ϳ2% for women, as defined by the ACR 1958 criteria (33). In a recent review of RA prevalence in the US, Lawrence and colleagues (13) reported that in the National Health Examination Survey (for the years 1960-1962), definite RA was identified in 1.8% of men and 4.9% of women between the ages of 65 and 79 years, using the ACR 1958 criteria for definite and classic RA.…”
Section: Discussionmentioning
confidence: 99%
“…This community-based program involved reviewing the medical history of residents from the area and a detailed physical examination. In subjects age Ն60 years, the prevalence estimates for "probable OA" were 17% for men and 29.6% for women based on history data alone (10).…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosen urinsyregikt bygget på om det hadde forekommet typiske artrittanfall og om anfallet var diagnostisert og behandlet av lege. Prevalensen var sammenlignbar med det som ble funnet i Tecumseh (Michigan) (1,3%) og New York (2,4%) (7,8). Sammenlignet med de ikke-skandinaviske urinsyregiktstudiene hadde individene i denne, høyere vekt, diastolisk blodtrykk og alkoholforbruk.…”
Section: Nordiske Landunclassified
“…Resultater fra regionale amerikanske populasjonsbaserte studier basert på ulike kriterier, er presentert i tabell 3 (7,(13)(14)(15). Den høyere prevalensen i Framinghamstudien skyldes en eldre populasjon sammenlignet med de to andre.…”
Section: Land Utenom Nordenunclassified